Mapping of Gross Heterogeneity of Mishrif Formation at West Qurna 1 Oilfield, Southern Iraq - Mustafa A. Abdulhasan; Amna M. Handhal ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study evaluates and maps the gross heterogeneity of the Mishrif Formation in the West Qurna-1 oilfield, southern Iraq, by counting the Lorenz coefficient (Lc) based on porosity, permeability, and thickness data from 99 wells. A custom Python script was utilized for data processing, and spatial interpolation was practiced using ordinary kriging in ArcGIS 10.8.2. The calculated Lc values range from 0.55 to 0.84, with an average of around 0.75, revealing a high to extreme degree of reservoir heterogeneity. Spatial distribution patterns indicate moderate heterogeneity in the northern sector, escalated heterogeneity in the central region, likely due to facies transitions, and extreme heterogeneity in the southern part, reflecting complex depositional environments and diagenetic alterations. These outcomes highlight the impact of heterogeneity mapping in optimizing well arrangement, enhancing sweep efficiency, and mitigating operational risks during reservoir development.DOI: https://doi.org/10.54633/2333-024-056-011